2013
DOI: 10.1666/12-076r.1
|View full text |Cite
|
Sign up to set email alerts
|

Timing and size selectivity of the Guadalupian (Middle Permian) fusulinoidean extinction

Abstract: A comprehensive, high resolution stratigraphic database of fusulinoidean foraminifers reveals that this group of protists suffered extreme losses during the Guadalupian extinction. Most species (88%) were eliminated gradually over the course of 9 myr during the Wordian and Capitanian ages. A pulse of greatly elevated per capita extinction frequency occurred during the last million years of the Capitanian (260–259 Ma). Contrary to prevailing opinion, the end-Capitanian event did not preferentially eliminate lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…This event is associated with shifts in the carbon and oxygen isotope record (Chen et al ., ) and a first‐order sea‐level lowstand (see Groves & Wang, , for a summary). Although there is still disagreement about the timing and main triggers of the end‐Guadalupian extinction (Clapham, Shen & Bottjer, ; Groves & Wang, ), it seems that the event is prolonged and possibly linked to a cool phase during the Capitanian (‘Kamura event’; Isozaki, Kawahata & Ota, ) as well as to the extrusion of the Emeishan Traps (southern China) and the sea‐level lowstand during the Capitanian–Wuchiapingian transition (e.g. Clapham & Payne, ; Wignall et al ., ; Groves & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This event is associated with shifts in the carbon and oxygen isotope record (Chen et al ., ) and a first‐order sea‐level lowstand (see Groves & Wang, , for a summary). Although there is still disagreement about the timing and main triggers of the end‐Guadalupian extinction (Clapham, Shen & Bottjer, ; Groves & Wang, ), it seems that the event is prolonged and possibly linked to a cool phase during the Capitanian (‘Kamura event’; Isozaki, Kawahata & Ota, ) as well as to the extrusion of the Emeishan Traps (southern China) and the sea‐level lowstand during the Capitanian–Wuchiapingian transition (e.g. Clapham & Payne, ; Wignall et al ., ; Groves & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, possible crises have been suggested for certain subsets of fishes, such as durophagous forms (Friedman & Sallan, ) or marine taxa (Pitrat, ). Little is known about the response of fishes to other extinction events of the Permian and Triassic, such as the end‐Guadalupian (Groves & Wang, ) and end‐Smithian crises (Galfetti et al ., ,b). Moreover, previous studies were only based on anecdotal evidence or primarily on data from old compendia, such as Benton () or Sepkoski ().…”
Section: Introductionmentioning
confidence: 99%
“…This calculation entails removal of the Signor-Lipps numbers restored to the Changhsingian. Possibly the Guadalupian event began before the end of the late Guadalupian (24,25), but close to the end of this interval there was heavy extinction of fusulinidoidean foraminiferans (13,(25)(26)(27). A recent thorough study of this group found that 88% its species that existed within the last million years of the Guadalupian became extinct by the end of this brief interval (27).…”
Section: Magnitudes Of Other Major Extinctionsmentioning
confidence: 99%
“…The brachiopods already have the strong early Lopingian aspect in the Laibin Limestone, and the changeover of brachiopods happened mainly between the late Capitanian Jinogondolella postserrata Zone and the J. xuanhanensis Zone (Shen and Shi, 2009), so did the changeover of rugose corals (Wang and Sugiyama, 2001). The fusulinids, on the other hand, suffered a heavy extinction of 88% species over an interval of 9 myr from the Wordian to the Capitanian (Groves and Wang, 2013). They persisted to the top of the Maokou Formation at the Tieqiao section , and then disappeared at the basal Heshan Formation, except Codonofusiella and Reichelina.…”
Section: The Changeover Of the Smaller Foraminiferal Fauna Near The Gmentioning
confidence: 99%